Compostos bioativos das partes aéreas de Evolvulus linarioides - Pereira, Laiane Caline Oliveira (2021)
Three new caryophyllane-type sesquiterpenoids, linariophyllenes A−C (1−3), two new hamamelitol derivatives, linaritols A (4) and B (5), two new chromones, linariosides A (6) and B (7), and three known chromones, cnidimol C (8), monnieriside A (9), and undulatoside A (10), were identified from the aerial parts of Evolvulus linarioides. The structures of these compounds were elucidated by NMR, MS, and IR data. The absolute configurations of compounds 1−5 and 7 were established via electronic circular dichroism data. The anti-inflammatory potential of compounds 1−5 and 7−10 was evaluated by determining their ability to inhibit the production of nitric oxide (NO) and proinflammatory cytokine IL-1β by stimulated J774 macrophages. Compounds tested at noncytotoxic concentrations inhibited NO production by macrophages, exhibiting IC50 values between 17.8 and 66.2 μM, and inhibited IL-1β production by stimulated macrophages by 72.7−96.2%.